Teachers’ Emotions and Experiences as Influential Factors in Using Technology in EFL Classes - Behzad Nezakatgoo; Fatemeh Mirzapour; Maryam Mohseni (Journal of Modern Research in English Language Studies)
Nowadays, technology plays an essential role in people’s life, in general, and in education, in particular. Teachers’ experiences and emotions can affect technology use in classes. The present study investigated teachers’ experiences and emotions regarding integrating technology into their classes. The study also explored teachers’ emotions toward institutional policies about using technology and the coping strategies they adopt for such emotions. Eleven teachers (five males and six females) from high schools of Tabriz, Iran, participated in the study. Five had a B.A., and six had an M.A. degree with six years of teaching experience. To collect data, semi-structured interviews were used. For analyzing the data, MAXQDA version 2022 was employed. The findings indicated that teachers had negative and positive experiences and emotions and employed various coping strategies to deal with their emotions. Their pleasant experiences involved accessibility of many resources, communicative learning, and improving teaching; while their unpleasant experiences included technical problems, learners’ low technological literacy, and teachers’ lack of technological training. Teachers’ debilitative emotions included being nervous, frustrated, and stressed but feeling capable, and enjoying were facilitative emotions. Besides, the teachers’ debilitative emotions toward institutional policies included feeling frustrated, and tired, and the facilitative emotions toward such institutional policies included feeling fulfillment and commitment. Teachers coped with emotions arising from the institutional policies about technology-enhanced EFL classes by asking for the help of colleagues, being patient/tolerating bad situations, and trying to control negative emotions. The present study offers some pedagogical implications for educational reformers, administrators, teacher educators, and teachers.